Seismic Characteristics of Paleo-Pockmarks in the Great South Basin, New Zealand - Karaket, Arunee; Chenrai, Piyaphong; Huuse, Mads (Frontiers in Earth Science, 2021)
Globally, a wide range of pockmarks have been identified onshore and offshore. These features can be used as indicators of fluid expulsion through unconsolidated sediments within sedimentary basin-fill. The Great South Basin, New Zealand is one such basin where paleo-pockmarks are observed at around 1,500 m below the seabed. This study aims to describe the characteristics of the paleo-pockmarks in the Great South Basin. Numerous paleo-pockmarks are identified and imaged using three-dimensional seismic reflection data and hosted by fine-grained sediments of the Middle Eocene Laing Formation. The paleo-pockmarks are aligned in a southwest to northeast direction to form a fan-shaped distribution with a high density of around 67 paleo-pockmarks per square kilometer in the centre of the study area. The paleo-pockmarks in this area have a similar shape, varying from sub-rounded to rounded planform shape, but vary in size, ranging from 138 to 481 m diameter, and 15 to 45 ms (TWT) depth. The origin of fluids that contributed to the paleo-pockmark formation is suggested to be biogenic methane based on seismic observations. The basin floor fan deposits beneath the interval hosting the paleo-pockmark might have enhanced fluid migration through permeable layers in this basin-fill. The model can help to explain pockmark formation in deep water sedimentary systems, and may inform future studies of fluid migration and expulsion in sediment sinks.